ADULTS’ ATTITUDES TOWARDS RECOGNITION OF NON-FORMAL AND IN-FORMAL LEARNING AT THE UNIVERSITY LEVEL - Burkšaitienė, Nijolė (Acta Paedagogica Vilnensia, 2007)
Assessment and recognition of non-formal and informal or so-called prior learning at the university level has recently become a new challenge for universities worldwide. Nowadays in Lithuania attempts are being made to create the system of recognition of non-formal and informal learning at the university level. Therefore, the issue of the quality of assessment of prior learning at the university level has become particularly important. The results of literature review provide enough proof that high standards of quality in the assessment of prior learning at the university level are predetermined by the proper choice of the assessment paradigm. Therefore, awareness of the differences between the positivist paradigm of assessment and the hermeneutic paradigm of assessment is crucial. The present research is aimed at analysing adults’ attitudes towards recognition of prior learning at the university level in Lithuania. The results of the study prove that in Lithuania adults’ attitudes towards such a possibility are positive. Study results show that adults’ age is the factor that influences their attitudes towards the possibility of participating in the process of recognition of prior learning at the university level, i.e. adults’ over 40 years of age are likely to be less active in this process than adults’ under 40 years of age. It has also been established that other factors, including the level adults’ education, their satisfaction with the current position, salary and career opportunities provided by the present job do not influence their attitudes. The results of the study prove that in Lithuania there exists adults’ need to have their prior learning assessed and recognized at tertiary institutions. It has been established that adults have much work experience, knowledge and skills gained in courses and studying autonomously in four major fields: management, social work, psychology and foreign languages. The finding that adults’ attitudes towards their participation in the process of recognition of prior learning at the university level are different across the four regions of Lithuania is important. What is more, this difference is statistically significant. This leads to the conclusion that adults’ articipation in this process is likely to depend upon the region.